Relapse in schizophrenia: a systematic review of criteria for clinical studies and international consensus guidelines to improve them : reviews and overviews - Howes, Oliver D.; Bukala, Bernard R.; Chen, Eric Y.H.; Correll, Christoph U.; Hasan, Alkomiet; Honer, William G.; Kane, John M.; Leucht, Stefan; Siafis, Spyridon; Agid, Ofer; Akena, Dickens; Arango, Celso; et al. (The American journal of psychiatry, 2025)
Objective: - Relapse prevention is a major goal of schizophrenia treatment. However, there is no standard definition of relapse. To address this, the authors reviewed recent approaches and developed consensus criteria to operationally define relapse. - Methods: - To evaluate current criteria, a systematic review was performed of randomized controlled trials of relapse conducted from 2012 to 2024. To develop consensus criteria, the authors used a multiphase Delphi approach involving over 100 experts from 37 countries, including people with lived experience of relapse. - Results: - The review showed only two pairs of studies that used the same criteria. Clinical judgment alone was sufficient to define relapse in 85% of studies, and 58% used relative symptom change. The recommended criteria cover the pre-baseline, baseline, and relapse components with optimum and minimum criteria and provide a reporting checklist. The recommendations include using standardized, validated measures that can be applied across settings, and using absolute symptom change. The authors also identify criteria that should not be used and make reporting recommendations, including for specific symptom domains (positive, negative, or cognitive) and across symptom domains, hospitalization, home treatment, and risky, violent, or suicidal behavior. - Conclusions: - There are limitations and heterogeneity in current definitions of relapse, which limit study comparisons, potentially bias meta-analyses, and question the validity of some studies. Adopting the consensus recommendations for a standardized approach should improve the validity and reliability of study outcomes, facilitate cross-study comparisons, and also standardize research into risk factors for relapse.
Online veröffentlicht: 8. Oktober 2025
Gesehen am 27.01.2026